Preferensi Konsumen Atas Atribut Aplikasi Mobile Banking Bank Syariah Indonesia Menggunakan Analisis Konjoin - Muhammad Ananda Lutgfi Sya’bana; Hairudinor (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2025)
Abstract: The research location was chosen in the city of Banjarmasin. 100 respondents were determined and selected using purposive sampling with the criteria of being Bank Syariah Indonesia users who actively use mobile banking. Questionnaires were used to collect conjoint data using a Likert scale. The results of the research show that there are six attributes in the Bank Syariah Indonesia mobile banking application with consumer preferences, namely the attributes of ease of use, level of security, completeness of features, Islamic features, application display design and application error rate, with the most important ranking being the security level attribute of 24.333 %, the application error rate attribute is 21.969%, the ease of use attribute is 20.367%, the online feature completeness attribute is 17.037%, the Islamic feature attribute is 10.234% and the application appearance design attribute is 6.067%.